Squamous cell carcinoma occurring in the wall of a chronic aspergilloma. Issue 7 (July 1991) - Andrew, S M; Bhattacharjee, M; Keenan, D J; Reid, H
Abstract : An aspergilloma that occurred within an area of bronchiectasis in a 52 year old man persisted for 12 years despite medical and surgical treatment. A squamous cell carcinoma developed in the wall of the cavity.